2007
DOI: 10.1186/gb-2007-8-11-r255
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate predictive and surrogate molecular markers for dasatinib in prostate cancer: Rationale for patient selection and efficacy monitoring

Abstract: Gene expression profiling was used to identify genes associated with sensitivity to the tyrosine kinase drug Dasatinib in prostate cancer cell lines, revealing a possible Dasatinib efficacy signature in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 41 publications
(55 reference statements)
7
78
0
Order By: Relevance
“…Earlier reports have shown that high expression of annexin-1, caveolin-1, caveolin-2, moesin, and uPA, as well as low expression of IGFBP2, was associated with the in vitro response to dasatinib in breast, lung, and prostate cancer cells (Finn et al, 2007;Huang et al, 2007;Wang et al, 2007). Here, we explored the association between the various biomarkers implicated in Src signalling pathways and the in vitro response to dasatinib in 73 human cancer cell lines, including the current 34 ovarian cancer cell lines and 39 breast cancer cell lines that have been published earlier (Finn et al, 2007).…”
Section: Predictors Of Dasatinib Response In Vitromentioning
confidence: 99%
“…Earlier reports have shown that high expression of annexin-1, caveolin-1, caveolin-2, moesin, and uPA, as well as low expression of IGFBP2, was associated with the in vitro response to dasatinib in breast, lung, and prostate cancer cells (Finn et al, 2007;Huang et al, 2007;Wang et al, 2007). Here, we explored the association between the various biomarkers implicated in Src signalling pathways and the in vitro response to dasatinib in 73 human cancer cell lines, including the current 34 ovarian cancer cell lines and 39 breast cancer cell lines that have been published earlier (Finn et al, 2007).…”
Section: Predictors Of Dasatinib Response In Vitromentioning
confidence: 99%
“…In addition, a baseline pharmacodiagnostic sample would be simpler to obtain from a routine diagnostic biopsy, for example, as opposed to posttreatment (pharmacodynamic) signatures where a separate biopsy procedure would be required. When comparing the pancreas cancer susceptibility gene signature for bosutinib described here to that for breast cancer (18) and prostate cancer (19) with dasatinib, we did not find shared genes. There are several possibilities to explain this difference.…”
Section: Discussionmentioning
confidence: 98%
“…The most obvious include different biology of breast and prostate cancer versus pancreas cancer, and cell lines versus cancer tissue that was explanted directly from the operating room into mice. In addition, it should be noted that comparisons between the breast and prostate cell line gene profiling data with dasatinib yielded a relatively small subset of shared genes, with only one (EphA2) shared in the limited gene set predictive model (19). Finally, although dasatinib and bosutinib share Src/Abl as a target, they have different chemical structures and inhibitory activity against the various Src family members (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dasatinib (Sprycel) is a novel, orally available, multitargeted, potent tyrosine kinase inhibitor that inhibits several critical oncogenic proteins, including BCR-ABL, SRC family kinases, c-KIT, PDGFR and ephrin A receptor kinase (Lombardo et al, 2004;Lee et al, 2005;Nam et al, 2005;Schittenhelm et al, 2006;Wang et al, 2007). Dasatinib has the greatest potency among the second-and third-generation tyrosine kinase inhibitors in vitro against ABL kinase activity (O' Hare et al, 2005;Quintas-Cardama et al, 2006), being 325-fold more potent than imatinib and 16-fold more potent than Therapeutic strategies for MPD C Kumar et al nilotinib.…”
Section: Ph( þ ) Mpd: CMLmentioning
confidence: 99%